Pregnancy Outcomes of Mothers with Detectable CMV-Specific IgM Antibodies: A Three-Year Review in a Large Irish Tertiary Referral Maternity Hospital. (30th November 2015) - Drew, Richard J.; Stapleton, Patrick; Abu, Hala; Healy, Eibhlín; Ferguson, Wendy; De Gascun, Cillian; O'Gorman, Joanne; Eogan, Maeve
Abstract : A retrospective audit was performed for all obstetric patients who had positive CMV IgM results between January 2012 and December 2014 in the Rotunda Hospital, Ireland. In total, 622 CMV IgM positive tests were performed on samples from 572 patients. Thirty-seven patients had a positive CMV IgM result (5.9%) on the Architect system as part of the initial screening. Three patients were excluded as they were not obstetric patients. Of the 34 pregnant women with CMV IgM positive results on initial screening, 16 (47%) had CMV IgM positivity confirmed on the second platform (VIDAS) and 18 (53%) did not. In the 16 patients with confirmed positive CMV IgM results, four (25%) had acute infection, two (12.5%) had infection of uncertain timing, and ten (62.5%) had infection more than three months prior to sampling as determined by the CMV IgG avidity index. Two of the four neonates of women with low avidity IgG had CMV DNA detected in urine. Both these cases had severe neurological damage and the indication for testing their mothers was because the biparietal diameter (BPD) was less than the 5th centile at the routine 20-week gestation anomaly scan.